2015
DOI: 10.3906/vet-1505-12
|View full text |Cite
|
Sign up to set email alerts
|

Breed, parity, and cycle season effects on life-timereproduction in bitches: a retrospective study

Abstract: IntroductionBitches are monoestrous, spontaneous ovulatory and traditionally nonseasonal mammalians, except for some breeds such as Basenji and Chow-Chow (1). The estrous cycle of the bitch is considerably longer than that of other domestic species and the estrous period is followed by a longer interestrous interval (diestrus and anestrus) (2). The interval is highly variable (2-10 months) among the breeds (3,4). Various factors that affect the interestrous period and pregnancy duration, such as breed, age, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The results of our study are in line with Eilts et al (2005), Mir et al (2011), andPolat et al (2015) who found a negative relationship between litter size and pregnancy length in large breeds as well. Our study documented for the first time the negative effect of gestation length on the number of live puppies born.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The results of our study are in line with Eilts et al (2005), Mir et al (2011), andPolat et al (2015) who found a negative relationship between litter size and pregnancy length in large breeds as well. Our study documented for the first time the negative effect of gestation length on the number of live puppies born.…”
Section: Resultssupporting
confidence: 81%
“…A combination of these (Mandigers et al 1994) stand behind the final numbers of puppies registered in kennel clubs, and parity of the bitch can be classified among the major factors (Borge et al 2011). Studies evaluating the effect of parity on litter size in different breeds revealed a significant influence of parity when only parity (not parity and breed) was incorporated to a statistical model (Borge et al 2011;Polat et al 2015). In Drever bitches kept as a colony in a private kennel, the litter size at the time of birth increased slightly from the 1 st to the 3 rd parity (Gavrilovic et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…According to breeds of bitches the levels of kisspeptin were (248.74 ± 11.53) pg/ml, (251.3 ± 10.76) pg/ml, (246.19 ± 10.1) pg/ml, (276.5216 ± 16) pg/ ml, and (241.6455 ± 6.9) pg/ml in German Shepherd, Belgian Malinois, Husky, Terrier and other breeds respectivelywith no significant. This result may be due the most breeds (German Shepherd, Belgian Malinois, Husky, Terrier) examined in this study considered as a non-seasonal pattern for estrous cycle (31)(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Polat et al . () reported that each additional puppy was associated with a 0.24‐day decrease in pregnancy duration. However, this association has not been confirmed in other studies (Linde‐Forsberg & Forsberg ; Kutzler et al .…”
Section: Discussionmentioning
confidence: 99%